Presence of Carbamazepine in coastal systems : effects on bivalves - Almeida, Ângela Augusta Soares de (2015)
Carbamazepine (CBZ), an antiepileptic drug, is one of the most commonly detected pharmaceutical drugs in aquatic ecosystems, being used as a marker of anthropogenic pollution. Since CBZ is designed to exert a biological effect, when it reaches aquatic environment high probability exists for toxic effects on non-target organisms. In this way, the present study evaluated the acute (96 h) and chronic toxicity (28 d) of environmentally relevant concentrations of CBZ (0.00, 0.03, 0.30, 3.00, 9.00 μg/L) in the edible clams Venerupis decussata (a native species) and Venerupis philippinarum (an invasive species) collected from the Ria de Aveiro lagoon. The effects on both species were assessed through the use of a battery of biomarkers mainly related with health status and oxidative stress in the organisms. Furthermore, it was applied a promising alternative technique, the immunoassay ELISA for the direct CBZ quantification in clams’ tissues. The results obtained for the acute test showed that CBZ levels in clams’ tissues increased along the exposure concentration range, where V. decussata accumulated more CBZ (except for CBZ 9.00 μg/L) than V. philippinarum. After an exposure of 28 d V. decussata accumulated a higher concentration of CBZ with exception of the highest concentration of exposure, where the levels of CBZ accumulated were similar to the acute test. Although the clams accumulated lower levels of CBZ than the concentration of exposure, these concentrations were enough to impair the health status of the species under study and induce oxidative stress. A different response to CBZ was observed for both species exposed to the acute test. V. philippinarum increased the lipid peroxidation levels at the highest CBZ concentration, whereas V. decussata presented a significant decrease in this parameter. Glutathione S-transferase activity was stimulated for V. decussata and decreased for V. philippinarum. Nevertheless, after exposure to CBZ, for both species it was found an induction of glutathione reductase and superoxide dismutase. The results indicated that, probably, V. philippinarum have a deficient antioxidant defense system compared with V. decussata, being less capable to neutralize reactive oxygen species and thus appeared to be the most sensitive species to the CBZ effects. A 28 d exposure to CBZ resulted in a higher toxicity in V. decussata compared with the same species exposed to the acute test. This was mainly reflected by a lower activity/content in the mechanisms involved in the antioxidant defense system and thus, a lower capability to lead with oxidative stress induced by CBZ. The risk quotient determined for the Ria de Aveiro was higher than 1 indicating that an ecotoxicolgical risk is suspected. Furthermore, the bioaccumulation of CBZ in clams should be taken into consideration since it might be transferred along the food chain, ultimately affecting humans.